2023
DOI: 10.3390/curroncol30060433
|View full text |Cite
|
Sign up to set email alerts
|

Can Molecular Biomarkers Help Reduce the Overtreatment of DCIS?

Abstract: Ductal carcinoma in situ (DCIS), especially in the era of mammographic screening, is a commonly diagnosed breast tumor. Despite the low breast cancer mortality risk, management with breast conserving surgery (BCS) and radiotherapy (RT) is the prevailing treatment approach in order to reduce the risk of local recurrence (LR), including invasive LR, which carries a subsequent risk of breast cancer mortality. However, reliable and accurate individual risk prediction remains elusive and RT continues to be standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…In addition, HER2 overexpression predicts a more effective response to RT for in situ LRs rather than for invasive ones [55,107,110].…”
Section: The Added Value Of Biomolecular Factorsmentioning
confidence: 99%
“…In addition, HER2 overexpression predicts a more effective response to RT for in situ LRs rather than for invasive ones [55,107,110].…”
Section: The Added Value Of Biomolecular Factorsmentioning
confidence: 99%
“…In addition, it can adversely affect cosmesis, quality of life, development of second cancer, and heart disease, not to mention the risk of financial toxicity for patients and their families. 55,56 Similarly, the use of endocrine therapy in the management of DCIS is inconsistent, which may be related to its lack of survival benefit and associated adverse effects 57 In an effort to use biomarkers to help de-escalate the treatment of DCIS, up to date, 3 molecular marker assays have been clinically evaluated in DCIS cases. [58][59][60][61][62] Oncotype DX DCIS Score Recognized as the first molecular expression assays evaluated for DCIS, Oncotype Dx is comprised of 12 of 21 genes of the Oncotype DX recurrence score.…”
Section: The Role Of Potential Molecular Biomarkers In Reduction Of T...mentioning
confidence: 99%
“…Breast radiotherapy can be associated with significant effects such as fatigue, skin erythema and desquamation, breast pain, skin telangiectasia, ulceration, and hyperpigmentation. In addition, it can adversely affect cosmesis, quality of life, development of second cancer, and heart disease, not to mention the risk of financial toxicity for patients and their families 55,56 . Similarly, the use of endocrine therapy in the management of DCIS is inconsistent, which may be related to its lack of survival benefit and associated adverse effects 57 …”
Section: The Role Of Potential Molecular Biomarkers In Reduction Of T...mentioning
confidence: 99%
“…Purswani et al [4] reviewed not only multi-gene profiling but also the classical low-tech parameters (e.g., age and tumor sub-type) considered when attempting to determine the cases for which omission is a reasonable strategy. Meanwhile, Hahn et al [5] wondered whether or not molecular biomarkers (three were evaluated in their review) could prevent the over-treatment of intraductal carcinoma of the breast. The authors observed that, in contrast to the case of invasive disease, very few protocols have been designed to pursue this type of research with DCIS.…”
mentioning
confidence: 99%